Information Technology-Based Financial Administration Training for Waste Bank Management - Supiin, Prima Prihatini (Universitas Ahmad Dahlan, 2023)
Background: Currently there are many movements to support the government related to improving people's welfare by processing waste. Since the Covid-19 pandemic, the price of used waste has decreased. This community service is carried out at the “Gemi Nastiti” Waste Bank. The recap of activities and finances carried out at the “Gemi Nastiti” Waste Bank is done manually, this is because members do not yet have the knowledge and ability to do administration. Therefore, this community service aims to provide assistance in preparing technology-based administration. Contribution: Providing knowledge, understanding, and financial administration skills to Waste Bank Managers